Trwamy . gazeta strajkowa, no. 13, 1981 - [ed. Jan Musiał] ([NSZZ "Solidarność"], 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished underground in 1984-1985 as the press organ of RKW NSZZ "Solidarność"